Benefits of dry firing and feedback in biathlon standing shooting practice - Isoaho, J. (University of Jyväskylä, 2023)
Introduction: Mastering biathlon standing shooting takes a lot of practice and the simultaneous demands of accuracy and speed when physically extorted are contrary requirements. There are very few training intervention studies found in biathlon research papers that studied the effects of shooting exercises or dry firing and feedback on biathlon shooting performance. To understand the effects of dry firing practice and feedback, the different forces acting between the shooter, the base and the rifle have to be assessed. The aim of this study was to investigate a feedback method for improving biathlon standing shooting skills and to motivate biathletes to practice dry firing at home. The second objective was to investigate the effects of the amount of dry firing practice on standing shooting performance. Finally, a comparison of standing shooting tests performed in the laboratory and on the shooting range was carried out to determine whether the results of dry and live shooting tests correlate, as no such data have been found from previous studies. Methods: Sixteen international- and national level biathletes were asked to perform standing shooting dry fire practice drills for eight weeks, eight subjects (MANTIS group, n = 8) with a Mantis X10 Elite (Mantis Tech, LLC, USA) shooting training device and eight subjects (CONTROL group, n = 8) without the Mantis device. A total of 1920 shots from 64 standing shooting tests were analyzed. The 30-shot standing shooting tests were performed both in the laboratory and on the shooting range before and immediately after the 8-week intervention period. Technical shooting parameters related to postural balance, aiming and triggering were also measured in the laboratory shooting tests. The training intervention consisted of 2 to 6 weekly dry firing exercises, performed at a time of the athlete's own choice. Other exercises were performed according to normal training programs. The Mantis shooting training device provided instant augmented feedback with sound and graphs, and long term statistics from the dry fire exercises to the MANTIS group athletes. The effects of the total amount of dry fire practice was examined by dividing the subjects into two groups based on the average amount of performed dry fire training. Correlations between dry and live fire tests were calculated for the whole group (N = 16) to investigate the effects of live fire recoil and sound on shooting performance. Results and Conclusions: The MANTIS group demonstrated more improvement with less training in live and laboratory standing shooting scores than the CONTROL group. Postural balance (standard deviation of the center of pressure location 0-0.6 s before firing) of the whole body in cross-shooting direction (SDX) and postural balance for rear (SDX_R) and front leg (SDX_F) decreased significantly (p < .05) in the MANTIS group. A high number of dry fire practice sessions was associated with better standing shooting performance both in the laboratory and on the range, and also with a higher amount of live fire training A small number of dry fire exercises showed greater variation in test results. Improvements in shooting range scores did not correlate with changes in laboratory shooting scores or technical variables. Range and laboratory shooting scores correlated only in post-tests (p < .001), indicating that results may vary with a new testing method, and skills learning stabilizes scores in laboratory tests. Future studies should compare laboratory and range tested scores and technical variables.